Differential Modulation by Akkermansia muciniphila and Faecalibacterium prausnitzii of Host Peripheral Lipid Metabolism and Histone Acetylation in Mouse Gut Organoids - Sabina Lukovac (American Society for Microbiology, 2014)
ABSTRACT The gut microbiota is essential for numerous aspects of human health. However, the underlying mechanisms of many host-microbiota interactions remain unclear. The aim of this study was to characterize effects of the microbiota on host epithelium using a novel ex vivo model based on mouse ileal organoids. We have explored the transcriptional response of organoids upon exposure to short-chain fatty acids (SCFAs) and products generated by two abundant microbiota constituents, Akkermansia muciniphila and Faecalibacterium prausnitzii. We observed that A. muciniphila metabolites affect various transcription factors and genes involved in cellular lipid metabolism and growth, supporting previous in vivo findings. Contrastingly, F. prausnitzii products exerted only weak effects on host transcription. Additionally, A. muciniphila and its metabolite propionate modulated expression of Fiaf, Gpr43, histone deacetylases (HDACs), and peroxisome proliferator-activated receptor gamma (Pparγ), important regulators of transcription factor regulation, cell cycle control, lipolysis, and satiety. This work illustrates that specific bacteria and their metabolites differentially modulate epithelial transcription in mouse organoids. We demonstrate that intestinal organoids provide a novel and powerful ex vivo model for host-microbiome interaction studies. IMPORTANCE We investigated the influence of the gut microbiota and microbially produced short-chain fatty acids (SCFAs) on gut functioning. Many commensal bacteria in the gut produce SCFAs, particularly butyrate, acetate, and propionate, which have been demonstrated to reduce the risk of gastrointestinal disorders. Organoids—small crypt-villus structures grown from ileal intestinal stem cells—were exposed to SCFAs and two specific gut bacteria. Akkermansia muciniphila, found in the intestinal mucus, was recently shown to have a favorable effect on the disrupted metabolism associated with obesity. Faecalibacterium prausnitzii is a commensal gut bacterium, the absence of which may be associated with Crohn’s disease. We showed that in our model, A. muciniphila induces stronger effects on the host than F. prausnitzii. We observed that A. muciniphila and propionate affect the expression of genes involved in host lipid metabolism and epigenetic activation or silencing of gene expression. We demonstrated that organoids provide a powerful tool for host-microbe interaction studies.